Minimizing Microbial Hazards for Fresh Fruits and Vegetables, Processing Water - Gast, Karen L. B.; Holt, Kim (My University, 2000)
This publication describes how water is used for fresh fruits and vegetables postharvest and how to get clean water.
MF2480_2000_12
Keywords: MF2480; Health and Safety; fruits and vegetables; MF